Pengaruh Penerapan Cooperative Learning Tipe CIRC (Cooperative Integrated Reading And Composition) dalam Keterampilan Membaca (Studi Eksperimen di MTs Madinatunnajah Cirebon) - Muna Mutamimah; Khasan Aedi; Maman Dzul Iman (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2021)
The purpose of this research is to find out students' reading skill in Arabic texts before and after the implementation of cooperative learning, CIRC (Cooperative Integrated Reading and Composition) type and to find out the effect of Cooperative Learning and the type is CIRC (Cooperative Integrated Reading and Composition) of students' reading skill in MTs Madinatunnajah Cirebon. This study used quantitative research as the method, specifically using experimental one-group pretest-posttest. Techniques of collecting data of this research were observation, question making and interview. Besides, the method to analyze the data of this research were statistical normality and hypothesis testing. The sampel were 2nd grade students of MTs Madinatunnajah Cirebon as many as 30 students. The findings from the analysis of students' reading skill in question making test which showed in the average of pre-test is 59.70 and post-test 76.30. The result of t - test sig (2-tailed) is 0,000 > 0,005, so it shows that there is an effect of implementation cooperative learning, Cooperative Integrated Reading and Composition (CIRC) type as the learning model to students' reading skill in Arabic texrs. There is also the effect on Cohen's formulation of 1.77 and it is in strong categories. This tertifies prove that there is a significant effect of Cooperative learning, CIRC type to students' reading skill in Arabic texts.